KONSEP KEADILAN DAN HUKUM DALAM PERSPEKTIF FILSAFAT HUKUM - Prista Alisa Ramadhani; Rasji . (Fakultas Hukum Universitas Islam Syekh Yusuf, 2022)
Law and justice are basically abstract, but not only based on the scope of philosophical study. Legal science always fights for justice. In reality, there is often a clash between legal certainty and expediency, or between justice and legal certainty, between justice and expediency. Talking about law and justice has to do with how justice can be implemented in the law itself. The law as the embodiment of the developed value referred to in this case is justice. The legal research method used is doctrinal. The embodiment of the value of justice is the existence of rights and obligations that can be fulfilled by the community itself. Where there is a rule of law, there are rights and obligations that govern it to create order and justice in society. The relationship between law and justice can be realized if the people themselves feel it. Laws and statutory regulations are basically symbols that are intrinsically and ideally containing truth and justice. Paradigm of legal positivism, justice is seen as a goal rather than law. Justice is seen as a goal rather than law, it's just that relativity often ignores another element, namely the element of legal certainty. Keywords: Philosophy Law, Justice, law